Inguinal vascular complications after ablation of atrial fibrillation: an economic impact assessment. Issue 1 (12th June 2018) - Bode, Kerstin; Ueberham, Laura; Gawlik, Susan; Hindricks, Gerhard; Bollmann, Andreas
Abstract: Aims: Ablation of atrial fibrillation (AF) is recommended in the guidelines as a Class Ia/IIa indication. However, associated complications should not be dismissed; specifically, inguinal vascular complications (IVC). Although IVCs are generally considered trivial, they represent an economic burden for the procedure-performing hospital and the patient. Therefore, the ability to monitor and ultimately minimize potential complications is of considerable interest. Methods and results: An economic model was developed to calculate the economic impact for certain IVC-types from a large German single-centre perspective in 2015 and 2016. Twenty-nine of 1040 (2.79%) and 48 of 1152 (4.17%) AF-ablation patients had documented IVC in 2015 and 2016 ( P = 0.08), respectively. Inguinal vascular complications that required invasive treatment (thrombin, intervention, surgery) occurred in 0.58% of the 2015 and in 0.87% of the 2016 AF-ablation cases. The expected excess costs (incorporating direct costs, benefit lost adjusted for reimbursement) per patient treated with AF-ablation were 139.54€ and 153.31€ in 2015 and 2016, respectively. This was mostly driven by opportunity costs, which could reach 15 544.71€ for certain IVC. Sensitivity analysis revealed the probability of occurrence, length of stay of certain IVC types, and the revenue per day influenced the expected costs per AF-ablation patient. Conclusion: Even relatively benign complications such as IVC can result in considerable cost increases. Therefore, measures to reduce them should be established and implemented.